Public institutions and enterprises and internal audit in the moroccan context - KERFALI , Souhaila (Revue Internationale des Sciences de Gestion, 2023)
In Morocco, public establishments and enterprises (EEP) play a major role in the economic and social development of our country because of their weight in the national economy and the place they occupy in the process of elaboration, planning and execution of public policies. The public establishments and companies are essential levers in the dynamics of economic and social transformation of the country. The take-off and dynamism of certain sectors of activity could not be achieved without their intervention. This article details the effectiveness of internal audit as practiced in the Moroccan public sector, describing the development of the Kingdom’s public sector. It also provides information on the functioning of the audit and external control bodies of public institutions and companies. The article also presents an overview of the development of internal audit practices in the Moroccan public sector and the regulations relating to the establishment and strengthening of internal audit in public institutions and enterprises.